Stem Cell Therapy for Veterinary Orthopedic Lesions - Barreira, Anna Paula Balesdent (2014)
Biomedical therapy has shown promising results in orthopedic lesions, providing replacement and repair descendants for normal turnover or injured tissues. This therapy includes stem cells, growth factors, natural and synthetic biomaterials, bank tissue, and engineered tissues. Regenerative medicine aims to harness the combined effects of a cell source, scaffold support, and anabolic stimulus to facilitate the healing of injury. Various cell sources have received attention, such as bone marrow (BM), adipose tissue (AT), peripheral blood (PB), and umbilical cord blood. This chapter reports what is known based on the current literature and the authors' experience, in order to contribute and define the full potential of stem cells. Although much has been discovered in regard to this new therapy, it still is a new technology and further studies are necessary, mostly with longer periods of follow-up studies.